Endocrine-disruptive Potential and Biochemical Effects of Cobalt on Juvenile Catfish (Clarias gariepinus) obtained from Aquaculture Facility in Akure, Ondo State, Nigeria - G. A. Ogunwole (Journal of Applied Sciences and Environmental Management)
Aquatic ecosystems are increasingly threatened by heavy metal pollution, with cobalt (Co) emerging as a dual-character element, essential as a micronutrient yet toxic at elevated levels. Hence, the objective of this paper was to evaluate the endocrine-disruptive potential and biochemical effects of cobalt concentrations of 1.8, 18, and 36 μg/L over 30 days on juvenile catfish (Clarias gariepinus) obtained from an Aquaculture Facility in Akure, Ondo State, Nigeria. Gene expression analysis revealed significant upregulation of key endocrine and stress-related markers. Cortisol (CORT) significantly upregulated only in fish exposed to 36 μg/L (111.69) compared to those in 1.8 μg/L (87.63), 18 μg/L (108.47), and the control group (96.15); hepatic vitellogenin (HVTG) significantly upregulated only in fish exposed to 36 μg/L (113.18) compared to those in 1.8 μg/L (88.71), 18 μg/L (104.45), and the control group (86.43); cytochrome P450 aromatase (CYP19A1B) significantly upregulated in the groups exposed to 18 μg/L (106.85) and 36 μg/L (107.31) compared to the control group (86.12); and peroxisome proliferator-activated receptor alpha (PPAR-α) significantly upregulated in the groups exposed to 1.8 μg/L (114.67), 18 μg/L (124.41), and 36 μg/L (112.74) compared to the control group (107.47), particularly at relatively higher cobalt concentrations. These changes suggest Co acts as an endocrine agonist, disrupting hormonal pathways through oxidative stress and estrogenic signaling. Biochemical analyses demonstrated non-monotonic dose-response effects on liver function enzymes. The alanine aminotransferase (ALT) levels in the 1.8 μg/L group (20.00 U/L) were significantly lower than those observed in the 18 μg/L (31.33 U/L), 36 μg/L (36.00 U/L), and control groups (35.33 U/L); aspartate aminotransferase (AST) levels in the 1.8 μg/L group (19.33 U/L) were significantly reduced compared to the 18 μg/L (30.67 U/L), 36 μg/L (31.33 U/L), and control groups (31.33 U/L); and alkaline phosphatase (ALP) levels in the 1.8 μg/L group (16.33) were significantly lower than those in the 18 μg/L (21.00), 36 μg/L (26.33 U/L), and control groups (30.67 U/L), respectively. Notably, lower Co concentrations elicited distinct metabolic responses compared to higher exposures. These findings highlight cobalt's capacity to alter hormonal regulation, metabolic processes, and liver function, even at trace concentrations, underlining its ecological and regulatory significance. This study provides crucial information of cobalt’s complex role as an environmental contaminant, emphasizing the need for stricter monitoring and management of heavy metal pollution in freshwater systems.